Multiple pulmonary nodules in malignancy. Issue 4 (July 2017) - Karki, Apurwa; Shah, Rakesh; Fein, Alan
Abstract : Purpose of review: Multiple pulmonary nodules are a common finding especially with the implementation of lung cancer screening. Available guidelines address the management of solitary pulmonary nodules. The management of the multiple pulmonary nodules would differ based on the characteristic of the nodules, their distribution, and the history of the patients as well. Recent findings: Most of the recent publications on multiple pulmonary nodules consist of individual case reports or case series. Robust population studies are lacking. Summary: In this article, we propose an approach for management of multiple pulmonary nodules which needs to be validated.